Effectiveness of computer-based cognitive rehabilitation on sensory profile, balance, and academic achievement of children with mild intellectual disabilities - Farzadmanesh, Mahdieh; Homaei, Rezvan; Jayervand, Hamdollah (Researcher Bulletin of Medical Sciences, 2025)
Objective: Children with intellectual disabilities (IDs) have deficits in sensory profile, balance, and academic achievement, which diminishes their adaptive functioning. The present study aimed to investigate the effects of computer-based cognitive rehabilitation on sensory profile, balance, and academic achievement of children with mild IDs. Materials and Methods: This was a quasi-experimental study with a pre-test-post-test design and a control group. The statistical population comprised all the elementary school students with mild IDs aged 7-11 years in Shiraz (Iran) in 2021-2022. A sample of 30 students was purposively selected and divided into two groups: a computer-based cognitive rehabilitation group and a control group (15 students per group). To collect data, the sensory profile, static and dynamic balance tests, and academic achievement were used. The data were analyzed using the analysis of covariance (ANCOVA) in SPSS v. 24. Results: There was a significant difference between the children with mild IDs in the computer-based cognitive rehabilitation and control groups in the sensory profile, balance, and academic achievement (P<0.01). Conclusion: Given that computer-based cognitive rehabilitation improved the sensory profile, balance, and academic achievement of children with mild IDs, parents and teachers are advised to use this method to enhance these children’s abilities in the mentioned domains.